Elucidating the Supramolecular Interaction of Positively Supercharged Fluorescent Protein with Anionic Phthalocyanines - Saarinen, Sharon; Khan, Ramsha; Patrian, Marta; Fuenzalida-Werner, Juan Pablo; Costa, Rubén D; Zimcik, Petr; Novakova, Veronika; Ruoko, Tero-Petri; Tkachenko, Nikolai V; Anaya-Plaza, Eduardo; Kostiainen, Mauri A (Advanced biology, 2025)
Developing bioinspired materials to convert sunlight into electricity efficiently is paramount for sustainable energy production. Fluorescent proteins are promising candidates as photoactive materials due to their high fluorescence quantum yield and absorption extinction coefficients in aqueous media. However, developing artificial bioinspired photosynthetic systems requires a detailed understanding of molecular interactions and energy transfer mechanisms in the required operating conditions. Here, the supramolecular self-assembly and photophysical properties of fluorescent proteins complexed with organic dyes are investigated in aqueous media. Supercharged mGreenLantern protein, mutated to have a charge of +22, is complexed together with anionic zinc phthalocyanines having 4 or 16 carboxylate groups. The structural characterization reveals a strong electrostatic interaction between the moieties, accompanied by partial conformational distortion of the protein structure, yet without compromising the mGreenLantern chromophore integrity as suggested by the lack of emission features related to the neutral form of the chromophore. The self-assembled biohybrid shows a total quenching of protein fluorescence, in favor of an energy transfer process from the protein to the phthalocyanine, as demonstrated by fluorescence lifetime and ultrafast transient absorption measurements. These results provide insight into the rich photophysics of fluorescent protein-dye complexes, anticipating their applicability as water-based photoactive materials.
Keywords: fluorescenční barviva; Organometallic Compounds; Energy Transfer; anionty; Luminescent Proteins; luminescentní proteiny; Anions; Zinc Compounds; Fluorescent Dyes; Spectrometry, Fluorescence; fluorescenční spektrometrie; sloučeniny zinku; Indoles; Isoindoles; přenos energie; organokovové sloučeniny; isoindoly; indoly